State of the Art and Future Trends in Material Modeling - Altenbach, Holm; Öchsner, Andreas (Advanced Structured Materials,, 2019)
This special anniversary book celebrates the success of this Springer book series highlighting materials modeling as the key to developing new engineering products and applications. In this 100th volume of "Advanced Structured Materials", international experts showcase the current state of the art and future trends in materials modeling, which is essential in order to fulfill the demanding requirements of next-generation engineering tasks. .